Analysis of the Degree of Information of Dental Surgeons about Antiresorptive Drugs According to the Time Since Graduation in Dentistry - Flávia Godinho Costa Wanderley Rocha; Roberto Paulo Correia de Araújo (Association of Support to Oral Health Research (APESB), 2023)
Objective: To determine the level of scientific information of dental surgeons who carry out their professional activities in Brazil about antiresorptive drugs and indicated pharmacological procedures aiming at the prevention of osteonecrosis of the jaws and the therapy of drug sequelae that may occur, considering the time since graduation in Dentistry. Material and Methods: This is a quantitative cross-sectional study in which 339 dentists were consulted using the virtual questionnaire containing topics of personal nature, elements contained in the anamnesis carried out and knowledge about antiresorptive drugs, including indications, adverse effects and treatments applied. Chi-square and Fisher's exact tests were performed to analyze associations of data described by absolute and relative frequencies with professionals' time since graduation. All analyses were performed using the R software, with a 5% significance level. Results: Those who revealed to have graduated for more than five years with the highest academic degree were those who demonstrated maximum knowledge of antiresorptive drugs or revealed that, somehow, they had information about them (p<0.05). Conclusion: Dental surgeons in Brazil who have more than five years since graduation have more scientific information about antiresorptive drugs and pharmacological procedures, which can positively contribute to the prevention of osteonecrosis of the jaws and treatment of drug sequelae that may occur.